Emerging Roles of GluN3B NMDA Receptor Subunit in the Central Nervous System - Yuerou Huang; Junyi Xie; Jiamin Chen; Siman Guo; Yuan Li; Fang Liu (Neuroscience Bulletin, 2026)
GluN3B is the most recently identified subunit of N-methyl-d-aspartate receptors (NMDARs), and gradually it has been found that it may be involved in regulating the development of central nervous system (CNS)-related diseases. Compared with the traditional NMDARs containing only GluN1 and GluN2 subunits, non-classical NMDARs with GluN3 have non-conventional biophysical, trafficking, and signaling properties. As a negative regulatory subunit that diminishes or inhibits classical NMDARs' functions, GluN3B plays important roles in synaptic plasticity and neuronal survival, and may be associated with CNS disorders such as schizophrenia and substance use disorders. However, the number and depth of studies on how GluN3B is involved in the regulation of related diseases are very limited. This review summarizes the expression and physiological characterization of GluN3B-NMDARs and provides an overview of their emerging roles in psychiatric and neuropsychiatric disorders, aiming to provide a basis for understanding disease mechanisms and developing novel therapeutic targets.

Dual-templates-assisted synthesis of hollow nanoreactors with hierarchically porous shell for efficient oxygen reduction reaction - Hao Li; Changge Shu; Guo Chen; Ruilian Hu; Erpan Qi; Yiyun Zeng; Siman Zhang; Kang Zhang; Kewen Tang; Kui Shen (Fuel, 2025)

Rapid geographical origin identification and functional compound content prediction of Chrysanthemum (“Gongju”) using excitation–emission matrix fluorescence spectroscopy coupled with chemometrics - Xue Guo; Youyou Wang; Ruibin Bai; Yao Chen; Siman Wang; Hui Wang; Yutong Hua; Tong Wang; Jian Yang (Food Chemistry, 2025)

Deferoxamine-induced neurotoxicity: Role of chaperone-mediated autophagy dysfunction in neuronal apoptosis in the hippocampus - Hong Zhang; Jian Guo; Jiayi Chu; Huanhuan Yu; Jialin Zhang; Siman Ma; Ge Jin; Yingshan Jiang; Jiao Xiao; Yutong Hou; Minyan Li; Shiliang Yin (Chemico-Biological Interactions, 2025)

Geographical verification of Pleuropterus multiflorus thunb. by functional compounds, stable isotope ratios, and multielement combined with machine learning methods - Feng Xiong; Siman Wang; Chuanzhi Kang; Youyou Wang; Ruibin Bai; Haiyan Li; Jian Yang; Lanping Guo (Food Chemistry, 2024)